Fractionation of hydro-ethanolic extracts from grape pomace through membrane processing: the effect of membrane and extracting media on process performance - Taqui, Syed Usman (2014)
The EM3E Master is an Education Programme supported by the European Commission, the European Membrane Society (EMS), the European Membrane House (EMH), and a large international network of industrial companies, research centers and universities